THE EFFECT OF STORAGE TIME AND ORIGIN OF RAW MATERIALS ON CPO QUALITY IN FFA, LAUNDRY AND MOIST PARAMETERS IN PKS INTI GUNA NABATI - Munandar, Iqbal Haris; Fachraniah, F; Sariadi, S (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACTIndonesia is currently the largest palm oil producer in the world with a production of around 3,855,000 tons/year in 2023. This study discusses the potential and quality of palm oil based on the duration of fruit storage (1, 2, 3, 4, 5, 6 and 7 days). The research was carried out from November to December 2023, at PT Inti Guna Nabati, Sarolangun, South Sumatra. The parameters measured for oil potential are crude palm oil (CPO) content, and the quality of palm oil measured is the bleaching regression index (DOBI), free fatty acid content, and moisture content from northern FFB suppliers (Rasau B2 Pamenang Village, Merangin District) and southern FFB suppliers (Setia Marg Village, Muara Lakitan District). Free fatty acids are determined by titration, and moisture content is measured with an electronic moisture analyzer. The purpose of this study is to find out the quality of the two FFB suppliers that are good and suitable for further processing at PKS IGUN. It will be better to bring FFB 1-2 days after harvest directly to the mill because the quality still meets the criteria of the IGUN mill. The results of the study show that the quality potential of FFB is the longer it is stored, the higher the FFA level, the lower the moist, the lower the DOBI. Based on the results of the study, the length of fruit storage has a bad effect on the quality of palm oil. Based on the results of CPO research from Rasau B2 Pamenang Village, Merangin District for FFA 2.13, moist 1.00 and DOBI 1.712, while the results of CPO research from Setia Marga Village, Muara Lakitan District are FFA 2.48, moist 0.47 and DOBI 1.681. Of the two research results, the CPO results from Rasau B2 Pamenang Village, Kec are better.Keywords : palm oil, FFA, laundry, moist